Variability in egg production of cod (Gadus morhua callarias L.) in the Central Baltic Sea - Kraus, Gerd (2002)
Recent findings indicate that stock size or stock biomass of expoited marine fish species does not reflect the true reproductive potential of a population. An explanation could be that the proportionality assumption between stock size and viable egg production inherent with many stock recruitment relationships is invalid. Using Eastern Baltic cod as a test species, the present study focuses on individual and population egg production in the Bornholm Basin, presently the only important spawning ground in the Central Baltic Sea. One major aim was the investigation of individual fecundity, its spatial and temporal variation and the underlying processes responsible for its variability. Another focus was the population egg production in the Bornholm Basin, which is addressed with special emphasis on the causes of fluctuations over the last 25 years. Ovarian atresia was investigated as a regulatory mechanism of fecundity, and hence, the population egg production.